Concentration-Dependent Pleiotropic Effects of Thymosin Beta4 and Cofilin on the Migratory Activity of Carcinoma Cells - Abdulatif Al Haj; Kamila Ćwikłowska; Antonina Joanna Mazur; Beate Brand-Saberi; Ewald Hannappel; Hans Georg Mannherz (International Journal of Translational Medicine, 2025)
Background/Objectives: Tumor cell migration depends on the actin cytoskeleton modified by actin-binding proteins (ABPs). Overexpression of cofilin or thymosin beta4 (Tß4) has been correlated with an increase or decrease in their migratory activity, respectively. Methods: Immunostaining of tumor cells and transfection with EGFP-tagged cofilin or bicistronic vectors leading to independent expression of EGFP and Tß4. Determination of cell migration by transwell or agarose drop assay. Results: We modulated by transfection the intracellular concentrations of cofilin and Tß4 of two colon (3LNLN and EB3) and one breast carcinoma (MDA-MB-231) cell line and analyzed their migratory activity. Increasing wild-type cofilin did not alter their migratory activity, whereas the constitutively active S3A–cofilin mutant elevated migration. Transfection leading to an up- or downregulation of Tß4 showed that MDA-MB-231 and 3LNLN cells responded with a decrease or increase in migration, respectively. Exposure of MDA-MB-231 and 3LNLN cells to increasing concentrations of extracellular Tβ4 (or His-tagged Tß4) induced a biphasic response of migration, being highest around 0.24 µM and decreased at higher extracellular Tß4. Immunostaining of 3LNLN cells exposed to 0.24 µM extracellular His-tagged Tß4 with anti-His antibody indicated its uptake co-localizing with integrin-linked kinase at cell attachment points. Furthermore, the exposure to 0.24 µM His-tagged Tß4 led to increased phosphorylation of AKT1/2 and secretion of matrix metalloproteases. These effects and tumor cell migration were abrogated after exposure of 3LNLN cells to 2.8 µM His-Tß4, also inducing apoptosis in a number of cells. Conclusions: Tumor cell migration can be inhibited by high extracellular Tß4.